Highly Overexpressed AtC3H18 Impairs Microgametogenesis via Promoting the Continuous Assembly of mRNP Granules - Xu, Liai; Liu, Tingting; Xiong, Xingpeng; Shen, Xiuping; Huang, Li; Yu, Youjian; Cao, Jiashu (Frontiers in Plant Science, 2022)
Plant CCCH zinc-finger proteins form a large family of regulatory proteins function in many aspects of plant growth, development and environmental responses. Despite increasing reports indicate that many CCCH zinc-finger proteins exhibit similar subcellular localization of being localized in cytoplasmic foci, the underlying molecular mechanism and the connection between this specific localization pattern and protein functions remain largely elusive. Here, we identified another cytoplasmic foci-localized CCCH zinc-finger protein, AtC3H18, in Arabidopsis thaliana. AtC3H18 is predominantly expressed in developing pollen during microgametogenesis. Although atc3h18 mutants did not show any abnormal phenotype, possibly due to redundant gene(s), aberrant AtC3H18 expression levels caused by overexpression resulted in the assembly of AtC3H18-positive granules in a dose-dependent manner, which in turn led to male sterility phenotype, highlighting the importance of fine-tuned AtC3H18 expression. Further analyses demonstrated that AtC3H18-positive granules are messenger ribonucleoprotein (mRNP) granules, since they can exhibit liquid-like physical properties, and are associated with another two mRNP granules known as processing bodies (PBs) and stress granules (SGs), reservoirs of translationally inhibited mRNAs. Moreover, the assembly of AtC3H18-positive granules depends on mRNA availability. Combined with our previous findings on the AtC3H18 homologous genes in Brassica campestris, we concluded that appropriate expression level of AtC3H18 during microgametogenesis is essential for normal pollen development, and we also speculated that AtC3H18 may act as a key component of mRNP granules to modulate pollen mRNAs by regulating the assembly/disassembly of mRNP granules, thereby affecting pollen development.